Price Discovery in Multiple-Dealer Markets: The Case of the Interbank Foreign Exchange Market - Karyn L. Williams (Claremont McKenna College, Department of Economics, 2000)
Price discovery is a principal function of financial markets. Yet, especially for dealership markets, financial economists know little about how prices are determined. In this paper I analyze the process of price discovery in the multiple-dealer, interbank spot market for foreign exchange. I use DM/ quotes to calculate interbank dealers' "information shares," their proportional contributions to the variance of innovations in the implicit, efficient exchange rate. These information shares are used to analyze relationships between price discovery and dealer characteristics. Unlike the U.S. equity markets, where regional exchanges contribute relatively little to price discovery, less-active interbank dealers play a large role, impounding most of the information into quotes. A pooled analysis of dealers' intraday information shares indicates that the lower the relative bid-ask spread and the greater the number of regional foreign exchange branches, the higher is a dealer's contribution to price discovery. Dealer nationality, however, does not appear related to price discovery within dealers' domestic markets.
Keywords: 330